SUSTAINABLE TOURISM SUPRANATIONAL POLICIES AND THE WELLBEING — GAPS AND CHALLENGES FROM THE HOSTS’ AND THE GUESTS’ PERSPECTIVE - Anna DLUZEWSKA; Jolanta RODZOS (Monitoring Obŝestvennogo Mneniâ: Ekonomičeskie i Socialʹnye Peremeny, 2018)
The year 2017 was declared by the United Nations General Assembly (UNGA) as the International Year of Sustainable Tourism for Development. Tourism is seen as a “driver of development and peace, promoting the harmonious co-existence of people from all countries” (Beijing Declaration 2016). A principle of sustainable tourism is to “build sustainable cities and communities”. From this perspective, tourism should support the wellbeing of all actors involved. Wellbeing of hosts, should be achieved when sustainable tourism guidelines are fulfilled. Wellbeing of guests is necessary to make any destination attractive for tourism. The question posed in this paper, however, challenges that view. The paper presents a theoretical analysis of wellbeing in relation to sustainable tourism and to hosting and guest communities. The first section talks about wellbeing conceptual backgrounds including Social Indicators, index of life quality based on values, subjective wellbeing or responsible wellbeing one. The second section focuses on the analysis of wellbeing in sustainable tourism conceptual background, including the differences between the guidelines provided by WTO (2005), and the latest guidelines published by UNWTO ((United Nations World Tourism Organization)) and UNGA in 2015. The third section juxtaposes wellbeing conceptual background with tourism, the most prominent gaps and challenges of wellbeing regarding hosting communities and tourists.